Characteristics and management of mechanically ventilated patients in South Korea compared with other high-income Asian countries and regions - Nam, Kyung Hun; Jeon, Kyeongman; Hong, Suk-Kyung; Leem, Ah Young; Ahn, Jee Hwan; Jang, Hang Jea; Byun, Ki Sup; Park, So Hee; Park, Sojung; Shin, Yoon Mi; Park, Jisoo; Kang, Sung Wook; et al. (Acute and critical care, 2025)
Background: This study investigated the characteristics of mechanically ventilated patients in South Korean intensive care units (ICUs). Methods: We conducted a subgroup analysis of a multinational observational study. Data from 271 mechanically ventilated patients in South Korean ICUs were analyzed for demographics, ventilation practices, and mortality, and were compared with those of 327 patients from other high-income Asian countries.Results: South Korean patients were older (mean age: 67 vs. 62 years, P<0.001) and had lower ratio of the partial pressure of arterial oxygen to the fraction of inspired oxygen (255.5 vs. 306.2, P<0.001). South Korean ICUs exhibited higher patient-to-nurse ratios (2.6 vs. 1.9, P<0.001) and more beds per unit (20.5 vs. 16.0, P=0.017). The use of sufficient positive end-expiratory pressure for patients (PEEP) for acute respiratory distress syndrome (ARDS) was less frequent in South Korea (62.2% vs. 91.2%, P=0.005). Mortality rates were similar between South Korean patients and those in other high-income Asian countries (38.0% vs. 34.2%, P=0.401). Significant mortality predictors in South Korea included age ≥65 years (odds ratio [OR], 4.03; P=0.039) and a Sequential Organ Failure Assessment score ≥8 (OR, 2.36; P=0.031). The presence of respiratory therapists was associated with reduced mortality (OR, 0.52; P=0.034).Conclusions: Despite higher age and patient-to-nurse ratios in South Korean ICUs, outcomes were comparable to those in other high-income Asian countries. The suboptimal use of sufficient PEEP with ARDS indicates potential areas for improvement. Additionally, the beneficial impact of respiratory therapists on mortality rates warrants further investigation.